“When You Come to Live in Switzerland, You Need to find it in itself and for itself”: The Swiss Idyllic Locus in the Interpretation of Mikhail Shishkin - Михайлова, Галина (Literatūra, 2016)
This article deals with the book of the Russian writer Mikhail Shishkin “Russian Switzerland”, a chapter from his travelogue “Following Byron and Tolstoy. Literary walk from Lake Geneva to the Bernese Alps” as well as some essays of the writer. Shishkin presents the image of Switzerland, which was formed in the Russian culture for several centuries. The author of the article notes the particular Shishkin’s position associated with his status as an expatriate. Shishkin reconstructs in Switzerland segments of Russian history and culture, thereby mitigating the stress of his own acculturation. Shishkin’s controversy with the Russian emigrants Solzhenitsyn and Brodsky are analyzed separately, as well as his relationship with Nabokov. The elements of the invaluable “discourse of Russia” in the travel notes of Shishkin are treated as a compensation for the resulting “deficiency” (the loss of Russia as a personal locus). Shishkin problematizes not only the relation of real Switzerland with Switzerland as a country-myth, but also his own hybrid identity as a resident of Switzerland. This identity is built in the space of “in beyond” of a homogeneous culture.
Keywords: Switzerland; discourse of Russia; expatriate; Solzhenitsyn; Brodsky; Nabokov; hybrid identity